Efektivitas Penanganan Orang Dengan Gangguan Jiwa Di Dinas Sosial Kota Palu - Rifai, Mohamad; Munari; Salingkat, Syarif Permana (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to evaluate the effectiveness of handling people with mental disorders (ODGJ) at the Social Service Office of Palu City. The focus of the research is directed at three indicators of effectiveness based on Richard M. Steers’ theory, namely: Goal Achievement, Integration, and Adaptation. This research uses a qualitative method with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation. The results of the study show that the Palu City Social Service has made several efforts, such as outreach activities, provision of social rehabilitation services, and cross-sector collaboration. However, the effectiveness of handling ODGJ still faces several obstacles. In terms of Goal Achievement, there is a lack of facilities such as temporary shelters for ODGJ. Regarding Integration, cross-sector coordination has not yet been fully optimized. In the Adaptation aspect, follow-up programs such as monitoring and assistance for ODGJ after being discharged from psychiatric hospitals are still lacking. The conclusion of this study indicates that the effectiveness of handling people with mental disorders by the Social Service Office of Palu City is not yet fully optimal. It still requires improvements in facilities, inter-agency coordination, and post-treatment support, particularly in the aspects of Goal Achievement, Integration, and Adaptation, in order to optimize services and create a more inclusive environment.